Synthesis of Waste Cooking Oil Based Bioadditive Through Transesterification and Its Feasibility as Lubricity Enhancer Bioadditives for Low-Sulfur Diesel Fuel: Preliminary Investigation - Yulfi Zetra; Rizka Berliana Rizka; Talitha Fitra Firdhausya; Yunita Alfiyati Firdausa; R. Y. Perry Burhan (Automotive Experiences, 2025)
Desulfurization of diesel fuel, which is considered to reduce pollution, causes a decrease in its lubrication power. As a result, the friction between surfaces of the engine increases, and it wears out easily. Therefore, it is necessary to increase diesel fuel lubricity through the addition of additives. Waste cooking oil modified to 2-hydroxypropyl esters has a prospect to be a lubricity-enhancing bioadditive. Polar and non-polar groups contain in 2-hydroxypropyl ester can form a bilayer on the surface of the engine that prevents friction between metal components. Synthesis of 2-hydroxypropyl esters was carried out by transesterification at 150Â°C for 10 hours. The mole ratio of oil to propylene glycol was adjusted to 1:7 with the loading of CaO 7% w/w oil as catalyst. The yield of the product is 88.89%. The product was identified by Gas Chromatography-Mass Spectrometry (GC-MS). The result showed that 2-hydroxypropyl palmitate and 2-hydroxypropyl oleate have dominant relative abundance with percentages of 42.46% and 57.44%, respectively. According to the molecular review as preliminary investigation, this compound has the potential to deliver better lubricity than ester-only biolubricants. Therefore, 2-hydroxypropyl ester can be proposed as an alternative bioadditive for low-sulfur diesel fuel lubricity enhancer.